Empatía - Goleman, Daniel; McKee, Annie, 1955-; Waytz, Adam (BookaVivo, 2022)
You need confidence to convey confidence, communicate effectively and be successful in your organization. But your own insecurities and fears can undermine your ability to act decisively and persuade others. What can you do to overcome those insecurities? This book explains how to use emotional intelligence to feel more confident at work and in your personal life.